Against the consensus : reflections on the great recession - Lin, Justin Yifu, 1952- (Cambridge : Cambridge University Press, 2013)
In June 2008, Justin Yifu Lin was appointed Chief Economist of the World Bank, right before the eruption of the worst global financial and economic crisis since the Great Depression. Drawing on experience from his privileged position, Lin offers unique reflections on the cause of the crisis, why it was so serious and widespread, and its likely evolution. Arguing that conventional theories provide inadequate solutions, he proposes new initiatives for achieving global stability and avoiding the recurrence of similar crises in the future. He suggests that the crisis and the global imbalances both originated with the excess liquidity created by US financial deregulation and loose monetary policy, and recommends the creation of a global Marshall Plan and a new supranational global reserve currency. This thought-provoking book will appeal to academics, graduate students, policy makers, and anyone interested in the global economy.
Preface -- Overview -- Part I. What Caused the 2008-9 Global Crisis?: 1. The world economy and the 2008-9 crisis -- 2. The real causes of the crisis -- 3. Financial deregulation and the housing bubble -- 4. What's wrong with the Eurozone -- 5. Why China's reserves rose so much -- Part II. A Win-Win Path to Recovery: 6. Infrastructure investments: beyond Keynesianism -- 7. A massive global infrastructure initiative -- Part III. How Poor Countries Can Catch up: Flying Geese and Leading Dragons: 8. The mystery of the great divergence -- 9. The mechanics and benefits of structural change -- 10. Lessons from the failures and successes of structural transformation -- 11. Unique opportunities for poor countries -- Part IV. Toward a Brave New World Monetary System: 12. The evolution of the international monetary system -- 13. Emerging pressures and policy challenges -- 14. (In)stability of the emerging multiple reserve currency system -- 15. The thinking behind the main reform proposals -- 16. Costs and benefits of major reform proposals -- 17. A proposal for a new global reserve currency: paper gold ('p-gold') -- 18. Why it still matters -- References -- Index.
Title from publisher's bibliographic system (viewed on 05 Oct 2015).
Keywords: Global Financial Crisis, 2008-2009.; Recessions -- History -- 21st century; China -- Economic policy